Ma'afu, prince of Tonga, chief of Fiji: The life and times of Fiji's first Tui Lau - Spurway, John (ANU Press, 2015)
Enele Ma`afu, son of Aleamotu`a, Tu`i Kanokupolu, grew up during a time of unprecedented social and political change in Tonga following the advent of Christianity. Moving to Lau, Fiji, in 1847 when he was about 21, he skilfully exploited kinship links to establish a power base there and in eastern Cakaudrove. His achievements were recognised in 1853 when his cousin King Tupou I appointed Ma`afu as Governor of the Tongans in Fiji. Acting as a putative champion of the lotu, Ma`afu undertook successful military campaigns elsewhere in Fiji and, after adding the Yasayasa Moala and the Exploring Isles to the nascent Lauan state, he was able to establish the Tovata ko Lau, a union of Lau, Cakaudrove and Bua, with himself as head. His power was formally recognised in 1869 when the Lauan chiefs appointed him as Tui Lau, a new title in the polity of Fiji. Ma`afu was now able to challenge Cakobau for the mastery of Fiji. After serving as Viceroy during the farcical planter oligarchy known as the Kingdom of Fiji, Ma`afu underwent a severe humiliation when, in order to maintain his power in Lau, he was forced to accede to the wishes of Fiji's other great chiefs in offering their islands to Great Britain. He would end his days as Roko Tui Lau, a 'subordinate administrator' in the Crown Colony of Fiji, presiding over a province characterised by corruption and maladministration but where the legacy of his earlier innovative land reforms has endured.